Strategies for Selecting Therapeutic Tactics for Reducing Transcutaneous Sensibilisation Risk in Infants with Atopic Dermatitis: Cohort Retrospective Prospective Study - Dmitri V. Fedorov; Nikolay N. Murashkin; Svetlana G. Makarova; Roman A. Ivanov (Педиатрическая фармакология)
Background. One of the key aspects in the development of atopic dermatitis (AtD) is epidermal barrier dysfunction leading to the penetration of pathogens and allergens through the skin with further body sensibilisation to them. Such pathological interaction can later on lead to the development of various allergic diseases in the child which not only worsen the course of atopic dermatitis itself, but also significantly reduce the quality of life of these patients. Objective. Aim of the study is to estimate the efficacy of therapeutic approaches for treatment of atopic dermatitis in reducing the transcutaneous sensibilisation risk in infants. Methods. The study included children aged 1 to 4 months with established AtD from moderate to severe forms. The severity of AtD was estimated via the EASI index. The level of specific IgE (sIgE) to food and domestic allergens was measured by the ImmunoCAP method using special reagents’ sets. The sensibilisation class was established depending on the sIgE index. Statistical analysis of the studied indexes shift and their comparison between the study groups was performed via multivariate analysis of variance (ANOVA). Results. The study included 81 patients. All patients were divided into two groups after basic AtD therapy with topical glucocorticosteroids (tGCS). Patients from study group № 1 received maintenance therapy with topical calcineurin inhibitor (TCI) (pimecrolimus 1%; PIM) for a long time, while patients from group № 2 continued to apply tGCS as proactive therapy. We have revealed that the level of sensibilisation to chicken protein and to the mixture of domestic allergens “domestic dust” was lower to the 12th month of life in group № 1 compared to group № 2 as a result of the data analysis. Children in group № 1 had faster and more significant decrease in the severity of AtD in comparison to group № 2 according to EASI index. Conclusion. Maintenance therapy including PIM is more efficient in reducing AtD severity and in prevention of transcutaneous sensibilisation in infants.